Ward D [large type] - McFadden, Freida (Thorndike Press large print high octane., 2025)
"Ward D is the hospital's mental health unit and as a medical student, Amy is required to gain experience on the floor. But little do her colleagues know it may force her to confront a past she's fought hard to forget. The night starts. The countdown begins. As the hours tick by, Amy grows increasingly convinced something terrible is happening within the ward's tightly secured walls. When patients and staff start to vanish without a trace, it becomes clear that everyone on the unit is in grave danger. Amy never wanted to spend the night on Ward D. Now she might not make it out alive"--